2014
DOI: 10.1007/978-3-642-55032-4_31
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Size of Forest Fire Using Hybrid Model

Abstract: Part 1: Information & Communication Technology-EurAsia Conference 2014, ICT-EurAsia 2014International audienceThis paper outlines a hybrid approach in data mining to predict the size of forest fire using meteorological and forest weather index (FWI) variables such as Fine Fuel Moisture Code (FFMC), Duff Moisture Code (DMC), Drought Code (DC), Initial Spread Index (ISI), temperature, Relative Humidity (RH), wind and rain. The hybrid model is developed with clustering and classification approaches. Fuzzy C-Means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Zwirglmaier et al (2013) used a BN to predict area-burned classes using historical fire data, fire weather data, fire behavior indices, land cover, and topographic data. Shidik and Mustofa (2014) used a hybrid model (fuzzy C-means and back-propagation ANN) to estimate fire size classes using data from Cortez and Morais (2007); the hybrid model performed best, with an accuracy of 97.50% when compared with naïve Bayes (55.5%), DT (86.5%), RF (73.1%), KNN (85.5%), and SVM (90.3%). Mitsopoulos and Mallinis (2017) compared BRT, RF, and LR to predict three burned-area classes for fires in Greece.…”
Section: Burned-area and Fire-severity Predictionmentioning
confidence: 99%
“…Zwirglmaier et al (2013) used a BN to predict area-burned classes using historical fire data, fire weather data, fire behavior indices, land cover, and topographic data. Shidik and Mustofa (2014) used a hybrid model (fuzzy C-means and back-propagation ANN) to estimate fire size classes using data from Cortez and Morais (2007); the hybrid model performed best, with an accuracy of 97.50% when compared with naïve Bayes (55.5%), DT (86.5%), RF (73.1%), KNN (85.5%), and SVM (90.3%). Mitsopoulos and Mallinis (2017) compared BRT, RF, and LR to predict three burned-area classes for fires in Greece.…”
Section: Burned-area and Fire-severity Predictionmentioning
confidence: 99%
“…Several computational intelligence approaches were used namely: Multilayer Perceptron (MLP), Radial Basis Function Networks (RBFN), Support Vector Machines (SVM) and fuzzy logic. Shidik and Mustofa [18] used a Back-Propagation Neural Network which was trained based on meteorological and forest weather indices, so as to classify the burned area in three categories. Aldrich et al [1] investigated the effect of variations in land use and climate in the occurrence of forest fires.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the 1990s, the surge in the availability of data and covariates has spurred the use of these techniques to predict wildfire behaviour. Jain et al (2020) found 127 journal papers or conference proceedings published up to the end of 2019 on ML applied to fire occurrence, susceptibility and risk; of these adversarial neural networks (ANN) were the most prominent (e.g., Liang et al, 2019;Dutta et al, 2013;Shidik and Mustofa, 2014). For wildfire occurrences, most studies focus on classification tasks instead of count modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Dutta et al (2013) explored different combinations of training-testing splits to identify the best possible paradigm to maximize the generalization capability of their ANN architecture. K-fold cross-validation is also popular (De Angelis et al, 2015;Shidik and Mustofa, 2014;Xie and Peng, 2019;Mitsopoulos and Mallinis, 2017), but it may give overly optimistic evaluations for spatially dependent data (Roberts et al, 2017). An alternative is spatial cross-validation (Pohjankukka et al, 2017), but it is still unclear how best to construct spatial folds in this context, and doing so anyway ignores time dependencies.…”
Section: Introductionmentioning
confidence: 99%